Photoexcitation in thin films deposited on silicon substrates by reactive pulsed laser ablation - A. Giardini Guidoni; V. Marotta; S. Orlando; G. P. Parisi (International Journal of Photoenergy)
Reactive pulsed laser ablation is a very interesting method to deposit thin films of several materials and compounds such as oxides, nitrides, semiconductors and superconductors. This technique relies on photoablation of pure elements, or a mixture of materials, with simultaneous exposure to a reactive atmosphere. In the case of oxides, reactions between the laser vaporized metals and oxygen lead to the formation of intermediate complexes and finally to oxide thin films. The reactivity of the plume has been already studied by our group in other oxides and nitrides productions and ascertained by Time of Flight Mass Spectrometry measurements [1].